Improving Family Knowledge And Attitudes On Malnutrition Through Family Centered Nursing-Based Modules And Videos - Heryyanoor Heryyanoor; Diana Hardiyanti; Melinda Restu Pertiwi (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: Education through media modules and instructional videos can improve families' knowledge of and attitudes toward malnutrition. Methods: This study uses a quasi-experimental research design, involving a pretest-posttest with a control group design. A sample of 74 families, divided into 37 families, were given education using learning modules and videos about malnutrition with family-centered nursing and 37 families as controls. The independent variables are learning modules and videos, while the dependent variables are knowledge and attitudes about malnutrition among families. The 30-question knowledge and attitude questionnaire about malnutrition that was given to families shows that it is valid and reliable. The Wilcoxon test was used to determine changes in the mean values before and after treatment. Results: After receiving treatment, respondents demonstrated an increase in their knowledge and attitudes. The mean value of knowledge increased by more than 30%, while the mean value of attitude statements increased by less than 10%, both of which exceeded the control group. The Wilcoxon p (0.001) test results were obtained before and after treatment administration for both groups. Conclusion: Providing education using joint learning modules and videos based on family-centered nursing is effective and can be carried out by nurses to increase family knowledge and attitudes about malnutrition.